Cataloging library resources an introduction - Shaw, Marie Keen (Library support staff handbooks, 2017)
Very few cataloging books are written specifically for library support staff. This is the only book purposefully aligned with the new American Library Association - Library Support Staff Certification (ALA-LSSC) competency standards for cataloging and classification. Written in clear language by someone who teaches cataloging in a library support staff program and featuring practical examples.